Progressive dopaminergic defect in a patient with primary progressive multiple sclerosis - Kaasinen Valtteri; Joutsa Juho; Rissanen Eero; Airas Laura; Soilu-Hänninen Merja; Noponen Tommi (Elsevier B.V., 2022)
Dopamine has a modulatory role in a number of autoimmune diseases, but there are no published cases of longitudinal dopaminergic imaging in multiple sclerosis (MS). Here we report a patient with primary progressive multiple sclerosis (PPMS) who was scanned twice with brain dopamine transporter single photon emission computed tomography (SPECT) with an interval of four years. The results showed a loss of tracer binding that corresponded to a 4–7 fold steeper decline than in normal ageing. The finding points to a relevant role of nigrostriatal dopaminergic degeneration in the pathological process of PPMS.